Intratumoral IL-28B Gene Delivery Elicits Antitumor Effects by Remodeling of the Tumor Microenvironment in H22-Bearing Mice. (28th July 2022) - Li, Zhi; Wang, Jianghua; Chen, Chong; He, Qi; Xu, Xiaoying; Da, Zejiao; Wang, Bo; Wang, Meng; Gao, Xiaotong; Zhang, Guochao; Gao, Qi; Si, Xiaoli; et al.
Abstract : IL-28B, belonging to type III interferons (IFN- λ s), exhibits a potent antitumor activity with reduced regulated T cells (Tregs) population, yet the effect of IL-28B on the tumor microenvironment (TME) and if IL-28B can downregulate Tregs directly in vitro are still unknown. In this study, we investigated the effects of IL-28B on Tregs in the spleen and TME in H22 tumor-bearing mice and verified the downregulation of IL-28B on Tregs in vitro . We found that rAd-mIL-28B significantly inhibited tumor growth and reduced the frequency of splenic CD4 + Foxp3 + T cells. The levels of CXCL13, ICAM-1, MCP-5, and IL-7 in the serum, and the levels of IL-15 and sFasL in the tumor tissue decreased significantly after rAd-mIL-28B treatment relative to rAd-EGFP. Furthermore, the percentage of CD8 + cells in the TME was significantly increased in the rAd-mIL-28B group compared with the untreated group. In vitro, splenocytes were stimulated with anti-CD3/CD28 and IL-2 in the presence of TGF- β with or without IL-28B for three days and followed by flow cytometric, RT-PCR, and IL-10 production analysis. The results showed that IL-28B significantly reduced the proportion of induced Foxp3 + cells. It demonstrated that IL-28B may be used as a promising immunotherapy strategy against cancer.